ANALISIS KESULITAN GURU BIOLOGI DALAM PELAKSANAAN PEMBELAJARAN JARAK JAUH (PJJ) DI SMA NEGERI PEKANBARU - Mei Satriana Ginting; Fitra Suzanti; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to analyze the difficulties of biology teachers in implementing distance learning at SMA Negeri Pekanbaru. This type of research is descriptive research. This research was conducted through the Pekanbaru Biology MGMP in May-June 2022. The sample was taken using purposive sampling, while the samples were 30 MGMP teachers with teaching criteria at Pekanbaru State High School and 30 students. The research instrument used in the form of a combination questionnaire to the teacher and a closed questionnaire to students. Before the instrument is distributed, it is validated by 3 lecturers until it is declared suitable for use. The results showed that the average percentage was 70% in the high category. Difficulties for teachers in implementing Distance Learning (PJJ) have difficulties such as limited time allocation hindering teachers in delivering material, learning methods that are difficult to adapt to current learning, making learning media for practical materials, lack of knowledge about electronic sources, and difficulties in monitoring student learning at home due to lack of cooperation between teachers and parents this is due to the busyness of parents with daily activities.Key Words: Teacher Difficulty, Distance Learning